Plant genetic resources in hot arid region - Bhatt, R. K.; Singh, J. P.; Rajora, M. P.; Saha, Dipankar; Kalia, Rajwant K. (Indian Farming, 2018)
Considering the complexity of the arid ecosystem, types and forms of available plant genetic resources, their sustainability under natural niches and the ecosystem services and livelihood support they provide, policy needs to address its importance at local and national level relating it to climate change mitigation, carbon accumulation and conservation. plant genetic resourcesconservation requires urgent awareness and extension involving local people’s participation. The major focus is required on: (a) Participatory mapping and monitoring of the areas having rich plant genetic resources of high value on which rural society depends for their livelihood. (b) Mapping of the niches where the plant genetic resources depletion is at alarming stage and needs conservation. (c) In situ and ex situ conservation, multiplication and documentation of the plant genetic resources. (d) Management and judicious uses of plant genetic resources rich areas and incentives/rewards to the rural communities for their role in conservation, management and protection of the area with capacity building through institutional support. (e) Creation of ‘Biodiversity Registers’ in villages. (f) Supporting public information and education campaigns on sustainability challenges and opportunities covering issues such as climate change and biodiversity conservation. (g) Digitization of plant genetic resources for accessibility of various users.